The prosody of presupposition projection in naturally-occurring utterances - Mahler, Taylor; de Marneffe, Marie-Catherine; Lai, Catherine (Proceedings of Sinn und Bedeutung, 2020)
In experimental studies, prosodically-marked pragmatic focus has been found to influence the projection of factive presuppositions of utterances like these parents didn’t know the kid was gone (Cummins and Rohde, 2015; Tonhauser, 2016; Djarv and Bacovcin, 2017), supporting question-based analyses of projection (i.a., Abrusán, 2011; Abrusán, 2016; Simons et al., 2017; Beaver et al., 2017). However, no prior work has explored whether this effect extends to naturally-occurring utterances. In a large set of naturally-occurring utterances, we find that prosodically-marked focus influences projection in utterances with factive embedding predicates, but not those with non-factive predicates. We argue that our findings support an account where lexical semantics of the predicate contributes to projection to the extent that they admit QUD alternatives that can be assumed to entail the content of the complement.